2003
DOI: 10.1046/j.1365-2419.2003.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Oceanographic variability and changes in Antarctic krill (Euphausia superba) abundance at South Georgia

Abstract: Oceanographic data collected to the north of South Georgia were examined for three consecutive summers (1996/97, 1997/98, 1998/99). The results show the existence of a shelf break front during each period. The most reliable means of defining the front was the potential density anomaly at the near‐surface potential temperature minimum. In each year, off‐shelf waters were separated from on‐shelf waters by water with a potential density anomaly between 27.22 and 27.29 kg m−3. During 1997/98, the near‐surface pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
121
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 44 publications
5
121
2
2
Order By: Relevance
“…The shelf break region has a major influence on water mass distribution to the north of South Georgia, with a frontal zone near the 500 m isobath between more productive, warmer, less stratified shelf water and colder more saline water off shelf ). This front is an area characterised by higher krill densities (Trathan et al 2003). The effect of travelling dives can be seen at both locations, with a higher frequency of shallower dives in shallow water, and at Cooper Bay close to the breeding beach.…”
Section: Discussionmentioning
confidence: 89%
“…The shelf break region has a major influence on water mass distribution to the north of South Georgia, with a frontal zone near the 500 m isobath between more productive, warmer, less stratified shelf water and colder more saline water off shelf ). This front is an area characterised by higher krill densities (Trathan et al 2003). The effect of travelling dives can be seen at both locations, with a higher frequency of shallower dives in shallow water, and at Cooper Bay close to the breeding beach.…”
Section: Discussionmentioning
confidence: 89%
“…Statistical analysis of environmental influences on krill distribution also revealed a consistent negative association with the distance to nearest land. Lascara et al (1999) At the finer scales of 0.5 km acoustic integration intervals, Trathan et al (2003) found no consistent effect of temperature, and instead bathymetry was the only consistent predictor of abundance, with abundance greatest near the shelf-break (similar to the qualitative summertime observations of Ichii et al, 1998 andPauly et al, 2000). Krill in summer may be associated with the shelf break in order to be positioned above CDW, due to the latter being favorable to successful spawning (Hofmann et al, 1992).…”
Section: 42c Environmental Associationsmentioning
confidence: 75%
“…Furthermore, GAMs proceed by fitting smoothing functions to the relationship between the response and each predictor variable, and thereby allow for nonlinear relationships (Hastie and Tibshirani 1990). The use of GAMs to examine associations between the results of acoustic surveys and environmental features has been employed previously for krill (Trathan et al, 2003), allowing interesting ecological insight.…”
Section: 25b Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Second, there is good background knowledge of this area, with extensive datasets on physics, nutrients, phytoplankton and krill (e.g. Whitehouse et al 1996, Brierley et al 1997, Trathan et al 2003, Meredith et al 2005.…”
Section: Introductionmentioning
confidence: 99%